Bibliographic Control of Electronic Resources and Metadata - Aytek Kaynak, Elif (Information World, 2001)
The rapid growth of the electronic resources on the Internet, both in quantity and quality, had lead the information retrieval problem to increase in the digital age. Current global search engines indexing the Web automatically via the programs being called "spider" and "crawler" use the terms derived from the fulltext, header etc. Other global searching mechanisms, such as Web directories are human generated and enumerate the subjects hierarchically under the related topics. However, both systems are inadequate tor efficient information retrieval on the Internet. The nature and variety of electronic resources underscore the need tor bibliographical control on the Internet. The purpose of this paper is to provıde an overview for the bibliographic control of the eıectronic resources and the metadata.
Keywords: Electronic resources; Bibliographic control; Search engines; Metadata; Dublin Core; Interoperability